Emerging Trends in Chemical Sciences - Ramasami, Ponnadurai; Gupta Bhowon, Minu.; Jhaumeer Laulloo, Sabina; Li Kam Wah, Henri; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Thirty carefully selected, peer-reviewed contributions from the International Conference on Pure and Applied Chemistry (ICPAC 2016) are featured in this edited book of proceedings. ICPAC 2016, a biennial meeting, was held in Mauritius in July 2016. The chapters in this book reflect a wide range of fundamental and applied research in the chemical sciences and interdisciplinary subjects. This is a unique collection of full research papers as well as reviews.
Chemistry of Natural Products -- Bioinformatics -- Material Science and Nanotechnology -- Computational Chemistry and its Applications -- Chemistry and Physics of Elemental 2D Materials -- Organic Chemistry -- Pharmaceutical Chemistry -- Green Chemistry -- Chemical Biology -- Analytical Chemistry -- Inorganic Chemistry -- Chemical Education -- Environmental Chemistry -- Polymer Chemistry -- Agricultural Chemistry -- Biophysical Chemistry -- Industrial Chemistry -- Medicinal Chemistry -- Physical Chemistry.
Keywords: Physical chemistry; Nanotechnology; Biochemistry; Environmental chemistry; Green chemistry; Physical Chemistry; Nanotechnology; Biochemistry; Environmental Chemistry; Green Chemistry